Energiewende und Megatrends: Wechselwirkungen von globaler Gesellschaftsentwicklung und Nachhaltigkeit - Engler, Steven; Janik, Julia; Wolf, Matthias (transcript, 2020)
Megatrends are major social developments - do they as such also have an impact on energy system transformation? And if so, what? An interdisciplinary view.